PROFIL KEMAMPUAN LITERASI NUMERASI, DIGITAL, DAN BUDAYA SISWA KELAS III UPTD SD NEGERI RIOMINSI - Melkior Wewe; Maria Efriliana Diru; Natalia Rosalina Rawa (JURNAL PENDIDIKAN DASAR, 2023)
Abstrak: This study aims to determine the profile of numeracy, digital and cultural literacy abilities of third grade students of UPTD SD Negeri Riominsi. This study uses data collection techniques by means of observation, interviews, and documentation. Where the data obtained were analyzed using qualitative descriptive methods. The subjects in this study were students of class III UPTD SD Negeri Riominsi totaling 13 people consisting of 3 boys and 10 girls. From the results of the researcher's observation data, it was found that the value of students' numeracy, digital, and cultural literacy skills was still located at 25% which was included in the low category. According to the interview results, the results of the fourth grade students' numeracy, digital and cultural literacy skills are still low, because not only students whose numeracy literacy skills are still at 25% but teachers also feel the same way. For digital literacy skills, it is still at 25% due to several things, including the lack of understanding of students about technology and teachers who have not been able to use technological tools during learning, while cultural literacy skills are still at 25% experienced there because in the learning process has not applied cultural literacy at all. based on data analysis on numeracy, digital, and cultural literacy skills, there is an increase where the increase is 50%. Keywords: Numerical Literacy, Digital Literacy, and Cultural Literacy Abstrak: Penelitian ini bertujuan untuk mengetahui profil kemampuan literasi numerasi, digital dan budaya siswa kelas III UPTD SD Negeri Riominsi. Penelitian ini merupakan penelitian kualitatif. Teknik pengambilan data dengan cara observasi, wawancara, dan dokumentasi. Dimana data yang diperoleh dianalisis dengan menggunakan metode deskriptif kualitatif. Subjek dalam penelitian ini adalah siswa kels III UPTD SD Negeri Riominsi yang berjumlah 13 orang terdiri dari 3 orang laki-laki dan 10 orang perempuan. Dari hasil data observasi peneliti di peroleh nilai pada kemampuan literasi numerasi, digital, dan budaya siswa masih terletak di 25% yang termasuk dalam kategori rendah. Menurut hasil wawancara diperoleh hasil kemampuan literasi numerasi, digital dan budaya siswa kelas III masih rendah, dikarenakan bukan hanya siswa yang kemampuan literasi numerasinya masih terletak di 25% tetapi guru juga merasakan hal yang sama. Untuk kemampuan literasi digitalnya masih terletak di 25%  disebabkan oleh beberapa hal yaitu diantaranya kurangnya pemahaman siswa tentang ala teknologi serta guru yang belum bisa menggunakan alat teknologi pada saat pembelajaran berlangsung, sedangkan untuk kemampuan literasi budaya masih terletak di 25% yang dialami di sana dikarenakan dalam proes pembelajaran belum diterapkan sama sekali literasi budayanya. berdasarkan analisis data tentang kemampuan literasi numerasi, digital, dan budaya terdapat peningkatan dimana peningkatannya menjadi 50%. Kata Kunci : Literasi Numerasi, Literasi Digital, dan Literasi Budaya